(untitled) (JS (JURNAL SEKOLAH), 2020)
Abstract : Improving Science Learning Outcomes through Experimental Methods and Learning Motivation SD Negeri 101739 Sei Mencirim. The purpose of this study was to determine the interaction between learning methods and learning motivation on science learning outcomes at SDN 101739 Sei Mencirim. This research method uses Quasi Experiment method with 2x2 factorial design. The results of the research analysis showed that the interaction between the Learning Method and students’ motivation to learn Science (Fcount = 5.228> Ftable = 3.13). The results of the study can be concluded that the experimental method is better used to teach students who have high learning motivation while the conventional method is good for students who have low learning motivation and there is an interaction between the experimental method and learning motivation. The implication of the results of this study shows that students taught with the Experimental Method have higher learning outcomes than students who are taught using conventional methods. Keywords : Experimental Methods, Learning Motivation and Science Learning Outcomes Abstrak : Peningkatan Hasil Belajar IPA Melalui Metode Eksperimen Dan Motivasi Belajar SD Negeri 101739 Sei Mencirim. Tujuan penelitian ini adalah untuk mengetahui interaksi antara metode pembelajaran dan motivasi belajar terhadap hasil belajar IPA di SDN 101739 Sei Mencirim. Metode penelitian ini menggunakan metode Quasi Eksperimen dengan desain faktorial 2x2. Hasil analisis penelitian menunjukkan bahwa interaksi antara Metode Pembelajaran dan motivasi belajar IPA siswa (Fhitung = 5,228>Ftabel = 3,13). Hasil penelitian dapat disimpulkan bahwa Metode Eksperimen lebih baik digunakan untuk membelajarkan siswa yang memiliki motivasi belajar tinggi sedangkan Metode Konvensional baik digunakan kepada siswa yang mempunyai motivasi belajar rendah dan terdapat interaksi antara Metode Eksperimen dan motivasi belajar. Implikasi dari hasil penelitian ini menunjukkan bahwa siswa yang diajarkan dengan Metode Eksperimen lebih tinggi hasil belajarnya daripada siswa yang dibelajarkan dengan Metode Konvensional. Kata kunci: Metode Eksperimen, Motivasi Belajar dan Hasil Belajar IPA